Improving The Safety And Quality Of Nuts. - Harris, L. (Woodhead Publishing in food science, technology, and nutrition., 2013)
As tree nuts and peanuts become increasingly recognised for their health-promoting properties, the provision of safe, high quality nuts is a growing concern. Improving the safety and quality of nuts reviews key aspects of nut safety and quality management. Part one explores production and processing practices and their influence on nut contaminants. Chapters discuss agricultural practices to reduce microbial contamination of nuts, pest control in postharvest nuts, and the impact of nut postharvest handling, de-shelling, drying and storage on quality. Further chapters review the va.